Prevalence and functions of non-suicidal self injury among young adults in higher institutions in Kedah - Annamallai, Madam Thangeswary; Mani, Kulanthayan KC; Ahmad, Norliza; Alimuddin, Aishah Siddiqah; Romli, Muhammad Hibatullah (BMJ Publishing Group, 2024)
Background: Non-suicidal self-injury (NSSI) is defined as the deliberate infliction of damage, pain or both to one’s own body tissue without the intention of suicide. NSSI is a prevalent problem within young adults throughout the world with the prevalence range of 8-22%. Different functions can underlie acts of NSSI. The four-function model (FFM) of NSSI was used to determine the objectives of this study. Objectives: The objective of the study was to determine the prevalence of NSSI behaviour and to determine the functions of NSSI and to determine the relationship between the functions of NSSI (based on the Four Functional Model of NSSI) and the NSSI behaviour among young adults of higher learning institutions. Methodology: In this study, cluster sampling in the population is divided into groups at various stages for better data collection, management, and interpretation involving 552 respondents. NSSI was assessed with the Functional Assessment of Self-Mutilation (FASM). The descriptive statistics were first conducted to examine the frequency and basic characteristics of NSSI in the sample selected. The demographic factors are described. Group comparisons was conducted using chi square test, X2 tests for the proportion of categorical measures and simple and multiple logistic regression test to find out the relationship between the variables. Results: A total of 27.5% young adults had reported self-injuring behaviour. A four-factor model of NSSI functions was indicated, with self-injurers likely to endorse both reasons of automatic reinforcement and social reinforcement. The most common reasons for NSSI were ‘to punish oneself, ‘to feel relaxed’, ‘to make others angry’ and ‘to stop bad feelings. It is found that their engagement in NSSI is to influence the behaviours of others and to manage internal emotions. Conclusions: In conclusion, there is an relationship between the ANR and APR and the NSSI behaviour. There is an relationship between the APR and ANR factors and NSSI behaviour among young adults in higher learning institutions in Kedah.